Penguatan Resiliensi, Inovasi dan Literasi Digital Womens Entrepreneur Pada UMKM Kota Padang Provinsi Sumatera Barat - Yendra, Nofri; Rosa, Yenni Del; Rajunas, Rajunas; Kurniawan, Rahmad (Universitas Dharma Andalas, 2024)
The research objective is to determine the influence of resilience, innovation and digital literacy of women entrepreneurs on the turnover of MSMEs in the city of Padang, West Sumatra province, partially and simultaneously. Research data comes from primary data using questionnaires from field research. This type of research is associative with a quantitative approach. The research population was 371 MSMEs and a sample of 189 MSMEs was determined by purposive sampling using the Rao soft sample size calculator software technique. Data collection methods using questionnaires, interviews and observations. Instrument test results and classical assumptions are met before the data is processed. The results of the multiple linear regression equation obtained Y = 0.211 + 0.497X1 + 0.715X2 + 0.248X3 + e. Partially and simultaneously, resilience, innovation and digital literacy of women entrepreneurs have a significant positive effect on the turnover of MSMEs in the city of Padang, West Sumatra province. Correlation of resilience, innovation and digital literacy of women entrepreneurs with turnover of 0.639 (medium) and Adjusted R square 0.372. Abstrak Tujuan penelitian mengetahui pengaruh resiliensi, inovasi dan literasi digital womens entrepreneur terhadap omset UMKM kota Padang provinsi Sumatera Barat secara parsial dan simultan. Data penelitian berasal dari data primer mengunakan angket berasal dari field research. Jenis penelitian bersifat asosiatif dengan pendekatan kuantitatif. Populasi penelitian 371 UMKM dan sampel 189 UMKM ditentukan secara purposive sampling menggunakan teknik software Rao soft sample size calculator. Metode pengumpulan data menggunakan angket, wawancara dan observasi. Semua hasil uji intrumen dan uji asumsi klasik memenuhi sebelum data diolah. Hasil persamaan regresi linier berganda didapat Y = 0.211 + 0.497X1 + 0.715X2 + 0.248X3 + e. Secara parsial dan simultan resiliensi, inovasi dan literasi digital womens entrepreneur berpengaruh positif signifikan terhadap omset UMKM kota Padang provinsi Sumatera Barat. Korelasi resiliensi, inovasi dan literasi digital womens entrepreneur dengan omset sebesar 0.639 (sedang) dan dan Adjusted R square 0.372.